On the conditions of formation of Southern Hemisphere tropical cyclones - Micheal T. Pillay; Jennifer M. Fitchett (Weather and Climate Extremes, 2021)
Tropical cyclones require high SSTs, instability and deep moist convection in order to form and intensify. The genesis conditions related to tropical cyclones in the Southern Hemisphere have been derived from global and historic studies, which by their generalist nature may conceal the true magnitudes of climate variables required for tropical cyclogenesis. This study updates and re-examines the previous tropical cyclone climatology with reference to the canonical works of Gray (1968, 1979). The optimal and minimum ranges of thermodynamic and dynamic climate variables following tropical cyclogenesis were determined, to define the conditions at which the majority of Southern Hemisphere tropical cyclones attain cyclone intensity. The SSTs of 27.5–28.5 °C is observed as the optimal range at which a majority of storms undergo genesis. However, the lowest observed magnitude at which cyclonic intensification was possible is 24 °C. This challenges the 26.5 °C threshold for genesis in the Southern Hemisphere. Based on factor analysis weightings and multivariate regression, SST, air temperature, geopotential height, components of vertical shear (u-wind) and relative humidity also account for a relatively large amount of variability in the intensification of tropical cyclones. Omega at the 1000 mb level and SST at the point of maximum intensity is important in promoting high magnitude storm intensification when initial SST during storm genesis is lower than 27.3 °C.